The role of the chicken gonadotropin-releasing hormone receptor C-terminal tail in expression and coupling - Lopes, John (Division of Medical Biochemistry and Structural Biology, 2018)
The role of the carboxy terminal tail of the chicken gonadotropin-releasing hormone receptor was determined by testing the activity of a series of chicken gonadotropinreleasing hormone receptors with progressive deletions in their carboxyl terminus. The 55 amino acid carboxy terminal tail of the chicken gonadotropin-releasing hormone receptor was progressively truncated, resulting in cS320STOP, cR330STOP, cS337STOP, cS346STOP, cT35ISTOP, cD356STOP, cS366STOP and cC375STOP truncated mutants, which were all tested in parallel with the wild type chicken gonadotropin-releasing hormone receptor. Truncation of the entire carboxy terminal tail from the chicken gonadotropin-releasing hormone receptor, cS320STOP abolished gonadotropin-releasing hormone binding and gonadotropin-releasing hormone-induced inositol phosphate production. The loss of gonadotropin-releasing hormone binding by the cS320STOP-truncated mutant suggests that this receptor is possibly not expressed on the cell membrane, which might be due to improper receptor folding by cS320STOP. The carboxy terminal tail of the chicken gonadotropin-releasing hormone receptor might therefore be required for proper folding of newly formed chicken gonadotropin-releasing hormone receptors and expression of these receptors on the cell membrane. The cR330STOP mutant had a maximal gonadotropin-releasing hormone binding of ~12%, which is the lowest receptor expression detected. The amino acid region between P³¹⁹ and L³²⁹ might therefore play a role in receptor expression. Progressive increase in the carboxy terminal tail from L³²⁹ resulted in progressive increase in the receptor expression. Maximal gonadotropin-releasing hormone binding levels reached wild type levels at truncation of the cGnRHR at S³⁶⁶. These results indicate that the first 45 amino region, ie. between P³¹⁹ and S³⁶⁶ of the chicken gonadotropin-releasing hormone receptor carboxy terminal tail contains elements that promote receptor expression. Gonadotropin-releasing hormone-induced inositol phosphate production was enhanced for all the truncated receptors except cR330STOP and cS337STOP, though all the truncated receptors had coupling efficiency values larger than the wild type chicken gonadotropin-releasing hormone receptor. This enhanced inositol phosphate production might be due to an increased coupling efficiency between the truncated chicken gonadotropin-releasing hormone receptors and the aq111-type G-protein. However, none of the truncated chicken gonadotropin-releasing hormone receptors have left-shifted EC50 values, indicating that coupling efficiency did not increase. Alternatively, a loss or retardation in receptor desensitization and/ or internalization for the truncated chicken gonadotropin-releasing hormone receptor mutants might be responsible for the enhanced gonadotropin-releasing hormone-induced inositol phosphate production by the truncated chicken gonadotropin-releasing hormone receptors. The chicken gonadotropin-releasing hormone receptor has a highly conserved cysteine residue in position 328 that might be palmitoylated. Replacing this cysteine in the chicken gonadotropin-releasing hormone receptor with an alanine [cC328A] increased receptor expression 2 fold, reduced maximal inositol phosphate production to ~69% and severely impaired coupling efficiency to 30% relative to the wild type levels. This finding indicates that C³²⁸ might be palmitoylated and is required for receptor coupling. In conclusion, the ammo terminal region of the chicken gonadotropin-releasing hormone receptor carboxy terminal tail increases receptor expression, either by affecting the transport of newly synthesized chicken gonadotropin-releasing hormone receptors to the plasma membrane and/or the proper folding of this receptor. The intracellular carboxy terminal tail of the chicken gonadotropin-releasing hormone receptor might play a negative role in G-protein coupling. However, the enhanced inositol phosphate production from the truncated chicken gonadotropin-releasing hormone receptors could be due to reduced internalization and/ or desensitization of the carboxy terminal truncated receptors. Point-mutation of C³²⁸ to A resulted in decreased coupling suggesting that C³²⁸ may be a palmitoylation site and might play a role in coupling or desensitization.